2016
DOI: 10.1074/mcp.m115.052332
|View full text |Cite
|
Sign up to set email alerts
|

Proteomes of the Female Genital Tract During the Oestrous Cycle

Abstract: The success of fertilisation in mammals is linked to the correct migration of spermatozoa in the different compartments of the female genital tract and the adequate timing of their interaction with the female gamete. In many mammalian species including human, the deposition of semen in the vagina is followed by the sperm migration through the cervix, the uterus and then the oviduct before reaching the site of fertilisation. This sperm transit within the female tract includes mechanical and biochemical interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
95
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 86 publications
16
95
0
1
Order By: Relevance
“…In addition, Moran et al () determined that the IGHA1 gene was downregulated in the endometria of dairy cows in oestrus. The proteins CFI and CD109 were both found to be more abundant in the cervical mucus of ewes in the luteal stage as opposed to during oestrus (Soleilhavoup et al, ). CFI has been described in humans as a component of the complement system (Xiang et al, ), while it has been proposed that CD109 may play a role in B cell–T cell interactions (Suciu‐Foca et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Moran et al () determined that the IGHA1 gene was downregulated in the endometria of dairy cows in oestrus. The proteins CFI and CD109 were both found to be more abundant in the cervical mucus of ewes in the luteal stage as opposed to during oestrus (Soleilhavoup et al, ). CFI has been described in humans as a component of the complement system (Xiang et al, ), while it has been proposed that CD109 may play a role in B cell–T cell interactions (Suciu‐Foca et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…AWN is not only secreted in the epididymis and by the seminal vesicles ( glandula vesiculosae ) of boars but even in the uterus, uterotubal junction and oviduct of sows (Ekhlasi‐Hundrieser et al., ). It was also found in the oviductal fluid of sheep (Soleilhavoup et al., ). Notably, the glycosylated form of AWN seems to originate exclusively from the seminal vesicles (Calvete, Solis, Sanz, Diaz‐Maurino, & Töpfer‐Petersen, ).…”
Section: Introductionmentioning
confidence: 79%
“…It has been demonstrated that the oviductal proteome changes with the different stages of the oestrous cycle (Lamy et al 2016; Soleilhavoup et al 2016), the presence of gametes (Georgiou et al 2005) or the presence of embryos (Smits et al 2017). The proteome of the oviduct epithelial cells has also been studied in humans (Wang et al 2016) and pigs (Seytanoglu et al 2008).…”
Section: Introductionmentioning
confidence: 99%